The Impact of Deferred Taxes Accountancy on the Accounting Profits Predictability- Empirical Study of a Group of Algerian Economic Enterprises - fennour, hanane; zirek, sewsan (Journal of Research in Finance and Accounting, 2021)
This study aims to know the extent of the possibility of using deferred taxes accountancy in predicting future profits. It also aims to know the impact of the sector that the enterprise belongs to and the size of its activity on the accounting profits prediction. To achieve that, 21 enterprises were selected from Algerian environment divided on a number of economic sectors. The study had used random effects model relied on financial data and financial statements of the sample’s enterprises for the financial period (2015-2018. So, the study concluded that the deferred taxes have an oppositely weak impact on the profits ability to predict the future cash flows, besides the relationship between the deferred taxes and the predictability of accounting profits doesn’t be affected by the type of economic sector and the size of economic enterprises.